Dental management of a pediatric patient with progressive familial intrahepatic cholestasis having dental anomalies: a case report and brief review of the literature - Mina Yazdizadeh; Maryam Sharifi; Arefeh Torabi Parizi; Firoozeh Alipour; Maryam Ghasempuor; Elham Zanguei; Maryam Yazdizadeh (BMC, 2023)
Abstract Background Progressive familial intrahepatic cholestasis is a heterogeneous group of disorders, leading to intrahepatic cholestasis, with the possibility of chronic liver failure and biliary cirrhosis. Oligodontia is either the manifestation of a specific syndrome or is non-syndromic. To the best of our knowledge, this is the first case report of type 3 progressive familial intrahepatic cholestasis and concurrent oligodontia, craniosynostosis, dens in dente, taurodontism, and delayed permanent dentition in the medical and dental literature. Case presentation We present the dental and medical histories and comprehensive dental management of a girl with type 3 progressive familial intrahepatic cholestasis and several dental anomalies, who was referred to a dental clinic due to severe dental caries and pain. Conclusion Our findings suggest that PFIC with manifestations as oligodontia, craniosynostosis, dens in dente, taurodontism, and delayed permanent dentition, might indicate an unknown syndrome; otherwise, the craniofacial anomalies are the manifestations of an independent disease coinciding with PFIC. Moreover, our case is a good example of the importance of timely medical and dental care in confining further health-related complications. The patient was able to ingest without any pain or discomfort after receiving proper dental management.